The Mormon people : the making of an American faith - Bowman, Matthew Burton (New York : Random House, 2012)
With Mormonism on the verge of an unprecedented cultural and political breakthrough, an eminent scholar of American evangelicalism explores the history and reflects on the future of this native-born American faith and its connection to the life of the nation. In 1830, a young seer named Joseph Smith began organizing adherents into a new religious community that would come to be called the Church of Jesus Christ of Latter-day Saints (known informally as the Mormons). Here, religious historian Matthew Bowman presents more than 180 years of Mormon history and doctrine. He recounts the church's origin and development, explains how Mormonism came to be one of the fastest-growing religions in the world by the turn of the 21st century, and sets the scene for a 2012 presidential election that has the potential to mark a major turning point in the way this faith is perceived by the wider American public--and internationally.--From publisher description.
Joseph Smith and the first Mormons : to 1831 -- Little Zions : 1831-1839 -- City of Joseph : 1839-1846 -- Come, come, ye saints : 1846-1877 -- The rise and fall of plural marriage : 1852-1896 -- Eternal progression : 1890-1945 -- Correlation : 1945-1978 -- Toward a global church : 1978-2011.
Includes bibliographical references (p. [295]-311) and index.
Keywords: Church of Jesus Christ of Latter-day Saints -- History; Church of Jesus Christ of Latter-day Saints -- History